Developing a Python program for investing using data from Chinese websites - Zheng, Xuguang (Nanyang Technological University, 2024)
In the dynamic environment of stock market investment, countless people are trying to invest their money in, aiming for a greater return in the future. Value investment is a widely known strategy to invest in stocks with high potential of growing in a mid to long term time prospect. A famous investor, Warren Buffet, is well known for his consecutive success in value investment which makes him one of the richest people in the world. As the economy in China prospered through the past decades, more and more people are interested in investing into the China A-shares. However, individual investors may be struggling in finding potential undervalued stocks for the long-term investments. This project presents the development of a Python-based tool designed to provide recommendations to investors based on calculations of the intrinsic values of the stocks in the market. Discounted cash flow (DCF) analysis is chosen as the quantitative model to assess the intrinsic value of the Chinese stocks. This project aims to develop a python program to make use of the valuation model as well as combining machine learning technologies in order to provide reliable recommendations with graphs and illustrations to the individual investors.